Investigation of prevalence and risk factors of subclinical mastitis of dairy buffaloes at Bhola district of Bangladesh - Aliul, Hasan; Kumar, Paul Ashit; Mahmood, Riad Mohammad; Mizanur, Rahman; Selim, Ahmed Md (Asian Journal of Medical and Biological Research, 2021)
The subclinical mastitis is more serious and is responsible for much greater loss to the dairy industry in Bangladesh. This study was performed to determine the prevalence of subclinical mastitis and identify the associated risk factors in randomly selected 200 lactating buffaloes (192 local and 8 crossbred) at some selected regions of Bhola district, Bangladesh during the period from March 2018 to February 2019. California Mastitis Test (CMT) was performed on each quarter milk sample of lactating buffaloes at field condition for the determination of subclinical mastitis in dairy buffaloes. Overall prevalence of subclinical mastitis was 10.50% (21/200). The prevalence of subclinical mastitis (SCM) was comparatively higher in crossbred (12.5%) as compared to local breed (10.42%). The highest prevalence of SCM in dairy buffaloes was also found in late lactation period (12.82%), age group 7 to 18 years (13.46%), rainy season (11.1%) and 2nd parity group (10.74%). Moreover, the buffaloes graze in free range areas; large and medium sized farms; poor health conditions and other diseases of post parturient period increasing the susceptibility of SCM. For early diagnosis of subclinical mastitis, CMT can be performed regularly as a control measures and emphasis should be provided on farm management practices; particularly on milking hygiene and udder sanitation. Asian J. Med. Biol. Res. December 2020, 6(4): 697-704